Towards Unified Literature Representations: Applications in Information Systems and Entrepreneurship Research (European Journal of Marketing and Economics, 2021)
Research activity is becoming increasingly complex due to the nature of research topics and questions. Among the essential academic research activities are literature reviews (LR), as they support the advance of the knowledge frontier. To improve literature reviews and their understanding, it would need to have comprehensive literature representations. In this perspective, the paper aims to advance previous work by illustrating a new way of creating thorough literature representations. The proposed tool is innovative and versatile since authors can adopt it in different types of LRs. Its adoption implies the construction of a three-dimensional scheme for the classification of the literature to be analysed. Then, based on the latter and selecting suitable evaluation variables, the proposed approach produces informative multidimensional representations for literature mapping and bibliometric analysis. For exemplifying this, the paper provides two application cases concerning Enterprise Resource Planning (ERP) systems and entrepreneurship research.
Keywords: literature review methodology, multidimensional representation, information systems, entrepreneurship, citation analysis